Implementasi Pendidikan Konstitusi untuk Memperkenalkan Eksistensi dan Peran DPR di Era Demokrasi Modern - yusrina handayani; Sitta Saraya (JURNAL INOVASI HASIL PENGABDIAN (JIHAN), 2026)
This community service program aims to increase public understanding of the existence and role of the House of Representatives (DPR) in a modern democracy through the implementation of constitutional education. Low political literacy and a lack of understanding of the function of representative institutions make it difficult for the public to participate optimally in the democratic process. The community service activities were carried out through several methods, including legal outreach and counseling, structured constitutional education, focus group discussions (FGDs), and interactive workshops in the form of legislative process simulations. Furthermore, mentoring was provided to participants to strengthen their ongoing understanding of the DPR's working mechanisms within the constitutional system. The results of the activities indicated an increase in participants' knowledge and awareness of constitutional values, the role of the DPR, and the importance of public participation in the oversight and implementation of democracy. Therefore, implementing constitutional education through a participatory approach can be a strategic step in building a more politically aware society and understanding of the DPR's position as a representative of popular sovereignty in the modern democratic era.